Electrochemical capacitive performance of thermally evaporated Al-doped CuI thin films. Issue 62 (8th December 2021) - Ghazal, Nurhan; Madkour, Metwally; Abdel Nazeer, Ahmed; Obayya, S. S. A.; Mohamed, Shaimaa A.
Abstract : Schematic diagram showing the preparation of the bare and Al-doped CuI thin films for supercapacitor applications. Abstract : In this paper, we studied the electrochemical capacitive performance of thermally evaporated copper iodide thin film doped with different quantities of Al (3, 5, 7, and 9 mol%). The morphological structure, crystalline nature, and surface composition of the deposited films with different dopant levels were confirmed using X-ray powder diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and field-emission scanning electron microscopy (FE-SEM). The electrochemical performance was evaluated based on cyclic voltammetry (CV), galvanostatic charge–discharge (GCD) measurements, and electrochemical impedance spectroscopy (EIS) in a Na2 SO4 electrolyte. The XRD results confirm that the film is crystalline and has a face-centered cubic structure. The SEM images revealed trihedral-tipped structures with irregular nanocubes. The presence of the trihedral-tipped structures is more obvious in the Al-doped CuI films than in the bare film. We report a progressive increase in the specific capacitance values as the aluminum content increases, from 91.5 F g −1 for the pure CuI film to 108.3, 126.2, 142.8, and 131.1 F g −1 for the films with aluminum content of 3, 5, 7, and 9 mol%, respectively at a scan rate of 2 mV s −1 . The optimized CuI-Al electrode with 7 mol% aluminum content showed remarkable long-term cycling stability with 89.1% capacitance retention after 2000 charge/discharge cycles. Such a high performance for the CuI-7Al film as a supercapacitor can be ascribed to the aluminum doping, which increases the electrochemically active area compared to the bare CuI film and is critical for electron exchange at the electrode/electrolyte interface. Therefore, we introduce CuI-Al as a viable option for supercapacitor applications because of its low-cost production, excellent electrochemical performance, and cycling stability.